Geomorphometric Analysis of Al -Teeb River Meanders Between Al-Sharhani Basin and Al-Sanaf Marsh, Eastern of Misan Governorate, Iraq - Bashar F. Maaroof /; Hashim H. Kareem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The current research deals with the morphology of river course meanders, which can be defined as one of the main geomorphological aspects of the course of the Al-Teeb river in the eastern parts of the Misan governorate, between Al-Sharhani basin and Al-Sanaf marsh. This phenomenon was studied according to the fundamentalist approach by analyzing the spatial relationship between this phenomenon and other natural factors such as the structure, surface, climate, and water resources that led to its occurrence. This relationship was inferred through the application of four morphometric equations for measuring this phenomenon, namely the sinuosity ratio, range and direction, symmetry ratio, and the meander wavelength to width ratio. The results showed that there are 16 meanders, the ratio of which ranged between 1.6 and 4.7, which represent the lowest and highest recorded values, respectively. Some of the meanders were characterized by high symmetry, as is the case with Al-Makhada 1 meander, while others had lower symmetry as with Al-Kiy’ad 1. for meander wavelength to width ratio values tended to differ according to the variation in erosion rates. DOI /10.54633/2333-021-042-033